Innovativeness, Risk-Taking, Proactiveness, and Firm Performance with Learning Organizations as Mediating Variables. - Kadarusman, Kadarusman; Rosyafah, Siti (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2022)
ABSTRACT This study aims to examine the mediating role of the learning organization variable on the influence of innovativeness, proactiveness and risk-taking on company performance in the Fashion Sub-Sector SMEs in East Java. This study uses a quantitative approach to test the research hypothesis and data processing using WarpPls 6.0. This research distributed questionnaires to company leaders as a representation of decision-makers, and the questionnaires analyzed in this study were 140 questionnaires. The results showed that innovative, risk-taking, and proactive directly affected learning organization and firm performance. Learning organization is proven to be a fully mediating variable, the effect of innovativeness, proactiveness, risk-taking on firm performance. The increase in the dimension of entrepreneurial orientation is expected to improve company performance. Increasing the dimension of entrepreneurial orientation can also make organizations always learn to adapt to an ever-changing environment. Keyword : Innovation, Proactive, Risk-Taking, Learning, Performance